The Solidarity of Humanitarian Activists in Addressing the Humanitarian Crisis in Papua: Understanding the Role of the Subject through the Lens of J.B. Metz's Political Theology - Pegan, Maximilian Boas; Langkeru, Frans Guna; Ngari, Ignasius; Ranubaya, Fransesco Agnes (Asosiasi Ahli Filsafat Keilahian Indonesia, 2025)
The humanitarian crisis in Papua, Indonesia, persists due to ongoing tensions between the state and indigenous Papuans. This crisis manifests in various forms, including war, horizontal conflicts, murder, arrests, violence, intimidation, and terror. These dehumanising conditions have led to the emergence of individuals and groups who stand in solidarity with those most affected, such as humanitarian activists from diverse backgrounds. Johann Baptist Metz highlighted the significance of solidarity as a cornerstone of his practical fundamental theology. Drawing on this theoretical framework, this study employs a phenomenological approach to explore and analyse the experiences of activists in Papua. The purpose is to capture the lived experiences of those who seek solidarity with vulnerable communities. The findings reveal that solidarity arises from a desire to help others, shared human values, and personal encounters with those who suffer. It develops across all social groups, among fellow sufferers or individuals from more privileged backgrounds.